2015
DOI: 10.1039/c5nr03349g
|View full text |Cite
|
Sign up to set email alerts
|

Single-excitation dual-color coherent lasing by tuning resonance energy transfer processes in porous structured nanowires

Abstract: Single-excitation dual-color coherent lasing was achieved in a mixed random system of a binary dye and the suspension of gold-silver porous nanowires with plenty of nanogaps. This greatly enhanced the local electromagnetic field in the visible range and guaranteed a low threshold and high Q factor (>10 000) operator for simultaneous dual-color lasing. By tuning the resonance energy transfer process in the stimulated emission, triple output modes (single chartreuse lasing, chartreuse and red dual-color lasing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…There are more spikes that emerged in the spectra as the pump power densities further increase, as shown in Figure 5A (blue and olive curves). The appearance of sharp spikes indicates building the coherent feedback in random system, resulting from the strong feedback and large enhancement of the local electromagnetic field induced by the nanogaps within Ag NFs [20][21][22]. The probability of coherent random lasing [37,38], defined as the ratio of the number of spectra with coherent modes to the total number of spectra captured, is used to determine the threshold of coherent random lasing as shown in Figure 5B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more spikes that emerged in the spectra as the pump power densities further increase, as shown in Figure 5A (blue and olive curves). The appearance of sharp spikes indicates building the coherent feedback in random system, resulting from the strong feedback and large enhancement of the local electromagnetic field induced by the nanogaps within Ag NFs [20][21][22]. The probability of coherent random lasing [37,38], defined as the ratio of the number of spectra with coherent modes to the total number of spectra captured, is used to determine the threshold of coherent random lasing as shown in Figure 5B.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Popov et al [14] found that gold nanoparticles enhanced the gain in random laser system containing dyes and gold nanoparticles. To achieve random lasing with lower threshold and multicolor emissions, nanogap-based random lasing was proposed by choosing the gold-silver (Au-Ag) bimetallic porous nanowires with abundant nanogaps that provide strong feedback or gain channels for coherent lasing from dye molecules [20,21]. Based on the strong confinement characteristic of the nanogaps, Au-Ag bimetallic nanowire-based random lasers operate at a low threshold and have high Q-factors in a wide visible spectral range [22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Demonstrations of random lasing have been reported with both pulsed and continuous-wave (CW) pumping. [4][5][6][7][8][9][10][11][12] Generally, long-wavelength or near-infrared (NIR) (>650 nm) uorescent dyes have high penetration properties in tissue. [13][14][15] Therefore, they can be fruitfully used for biomedical and biophotonic applications, such as in surgical therapy treatments, cancer diagnostics, etc.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Such optically active biodegradable organic dyes provide a unique possibility for RL generation in combination with metal/semiconductor nanoparticles (NPs) as the scattering particles. [4][5][6][21][22][23] Traditionally, it has been reported that, RL generation is dependent on multiple scattering of light in a random gain medium. The presence of the strong electric eld of metal NPs may enhance these scattering properties, and may also modify the transition rates of nearby dye molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation